Comparative study of different PWM control scheme for three-phase three-wire shunt active power filter - A.S.A. , Hasim; Zulkifilie, Ibrahim; Hairul Nizam, Talib (2012)
Instantaneous reactive power theory was the most popular control theory used when dealing with harmonics compensations. In conjunction with the instantaneous theory, switching signal generation techniques plays an important role to ensure the correct compensation signal injected in the system. Therefore, this paper discussed on comparative study of five (5) methods used in instantaneous theory namely; p-q method, modified p-q, d-q method, p-q-r method and vectorial with three (3) types. of signal generation namely; carrier current control, hysteresis current control and space vector modulation control. Continuous reductions of the total harmonics distortion (THD) are expected at the supply current when applied different types of switching technique. The compnrison was examining using MATLAB/Sirnulink (MLS) environment.